Corporate social responsibility in the information society: features of personnel management in the 21st century - A. A. Madyarov (Вестник университета)
The increasing role of knowledge in modern society actualises the creation of conditions for the formation and redistribution of information resources. Implementation of Internet economy principles has a positive effect on both economic and social performance indicators of Russian companies. The positive effect is manifested not only in the growth of revenue volumes of companies but also in their increasing corporate social responsibility. In this regard, the study of management methods in telecommunications and industrial production – sectors that are critical to the 21st century’s economy – is of particular importance. Increasing employees’ responsibility by elevating their engagement, which can be achieved through granting them additional rights, contributes to the formation of a team with such internal motivation that is most effective and valuable for a modern company. Redistribution of operational power between interest groups makes the interests of all performers unite around the goals of the organization.